Synthesis of Graphite Paste/Molecularly Imprinted Polymer (MIP) Electrodes Based on Polyeugenol as a Glucose Sensor with Potentiometric Method - Muhammad Cholid Djunaidi; Mei Dian Risda Afriani; Gunawan Gunawan; Miratul Khasanah (Universitas Gadjah Mada, 2021)
Diabetes mellitus is a chronic disease in which the body is unable to metabolize carbohydrates, fats, and proteins. In this study, eugenol was polymerized and then contacted with glucose and crosslinked using polyethylene glycol diglycidyl ether (PEGDE). The resulted PE-Glucose-PEGDE was eluted using ethanol to form MIP-Glucose. It was then characterized by FTIR, SEM, electrodes using the Eutech 510 potentiostat and UV-Vis spectrophotometer. The result of polyeugenol synthesis is a reddish-brown powder with a yield of 99.90% and a molecular weight of 6318.033 g/mol. UV-Vis spectrophotometer analysis showed that the contacted glucose was 2152.505 ppm. SEM results showed differences in the surface morphology of the material, indicating the formation of cavities in MIP and ESM, while no cavities are found in NIP and ESN. The electrode optimization resulted in the best composition ratio of MIP 1 mol: paraffin: graphite, respectively of 20:35:45. The resulting electrode has a Nernst factor of 20.24 mV/decade with a measurement range of 10–5–10–1 M, a limit of detection value of 8.363 × 10–5 M, and the value of the selectivity coefficient (Kij) of the electrodes in a (10–5–10–1) M fructose solution was 0.3733; 0.23048; 0.17864; 0.12359; 0.1073.